Traffic safety and dynamic properties of the bridge deck of high-speed railway lines - V. Yu. Polyakov; Dang Ngoc Thanh (Вестник Научно-исследовательского института железнодорожного транспорта)
Abstract. High-speed lines are one of the safest modes of transport, despite the special conditions for moving the wheel along the rail. The urgent task is to ensure the sustainable motion of the wheel along the rail over the bridges in high-speed traffic. A feature of high-speed lines (HS lines) is the practical achievement of critical speeds that cause resonance of bridge deck structures. Cases of rolling stock derailments on high-speed lines are not frequent. The article provides information about rolling stock derailments on high-speed rail and its consequences. Standards for the stability of wheels on rails in various countries with high-speed rail were considered. On the bridges of high-speed lines there are not many elements of the track that are strong dampers — the roadbed, its base and ballast. Due to the lack of damping elements, the damping properties of the bridge deck are of great importance. When driving over the bridge with critical speeds causing near-resonance oscillations, the force in the wheel—rail contact may drop to zero with the risk of derailment. Insufficient damping poses a threat to traffic safety. Thus, one of the most important dynamic parameters — damping — is a problem for a ballastless track on high-speed railway bridges. Considerations are given for the correct determination of stiffness associated with damping and affecting the interaction of rolling stock and bridge deck. It is shown that in case of insufficient damping at the fastening points on the bridges, the risk of derailment increases due to a fall of the vertical force below the permissible limit at the wheel—rail contact. Results of computer performed experiments are presented, confirming that it is precisely the significant oscillations of the bridge deck structures that are a safety hazard, since when the first car passes, the force at the contact of the wheel and rail for the first wheelset is safe. Requirements for damping parameters are given, ensuring reliable contact of the wheel and rail with significant fluctuations in bridge deck structures on high-speed lines. Results are presented, showing the dependence of required damping on the stiffness of intermediate rail fasteners.